Approximating properties of biharmonic Poisson operators in the classes $\hat{L}^{ψ}_{β, 1}$ - Zhyhallo, T. V.; Kharkevych, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We obtain the asymptotic equalities for the least upper bounds of the approximations of functions from the classes $\hat{L}^{ψ}_{β, 1}$by biharmonic Poisson operators in the integral metric.